Comparison of ABR and ASSR using NB-chirp-stimuli in children with severe and profound hearing loss. (April 2020) - Eder, Katharina; Schuster, Maria Elke; Polterauer, Daniel; Neuling, Maike; Hoster, Eva; Hempel, John-Martin; Semmelbauer, Sebastian
Abstract: Introduction: Objective techniques for hearing threshold estimation in infants and children with profound or severe hearing loss play a key role in pediatric audiology to prevent speech acquisition disorders by choosing the adequate therapy. Auditory brainstem responses and auditory steady-state responses are available for frequency-dependent hearing threshold estimations and both techniques show strong correlations. However, various systems and stimuli are available, which is one reason why comparison is challenging, and, so far, no single "gold standard" could be established for hearing threshold estimation in children suffering from profound or severe hearing loss. The aim of the study was to compare hearing threshold estimations in children with profound or severe hearing loss derived with narrow-band CE-chirps evoked auditory brainstem responses and auditory steady-state response. Subjects: and Methods: 71 children (121 ears) with an age from 3 month to 15 years were measured with the Interacoustics Eclipse EP25 ABR system® (Denmark) with narrow-band CE-chirps® at 500, 1000, 2000 and 4000 Hz under identical conditions. Results: Auditory brainstem responses and auditory steady-state responses highly correlate (r = 0.694, p < 0.001). Correlation coefficients differ depending on the center frequency and patient age. Generally, auditory steady-state responses show a better hearing threshold than auditory brainstem responses or a remaining hearing threshold when auditory brainstem responses could not be obtained. In approximately 15% of cases this would have affected the therapeutic strategy when only taking one technique into account. Conclusion: Auditory brainstem responses and auditory steady-state responses should be jointly used in the diagnostic approach in children with suspected profound or severe hearing loss.